Shear Strength of Reinforced Concrete Columns Retrofitted by Glass Fiber Reinforced Polyurea - Jun-Hyeok Song; Eun-Taik Lee; Hee-Chang Eun (Salehan Institute of Higher Education, 2020)
Aged structures and structures constructed based on outdated non-seismic design codes should be retrofitted to enhance their strength, ductility, and durability. This study evaluates the structural performance of reinforced concrete (RC) columns enhanced via polyurea or glass fiber reinforced polyurea (GFRPU) strengthening. Four RC column specimens, including a reference specimen (an unstrengthened column), were tested to evaluate the parameters of the strengthening materials and the strengthened area. The tests were carried out under a combined constant axial compressive load and quasi-static cyclic loading. The experimental results show that the composite strengthening provides lateral confinement to the columns and leads to enhanced ductility, shear-resistance capacity, and dissipated energy. The shear strength provided by the composites depends on the degree of lateral confinement achieved by the composite coating. The specimens finally failed through the development of diagonal tension cracks within the potential plastic hinge regions. The specimen treated with GFRPU strengthening showed greater strength and dissipated more energy than the specimen treated with polyurea strengthening. Furthermore, by modifying ATC-40, this study proposed an equation to estimate the shear capacity provided by the composites.